2006
DOI: 10.1007/s00281-006-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

IgA and IgA-specific receptors in human disease: structural and functional insights into pathogenesis and therapeutic potential

Abstract: IgA antibodies play an important role in humoral immunity. IgA is the predominant antibody in mucosal secretions and the second most prevalent in the serum. It occupies a unique position among human antibodies in that it can both trigger and suppress inflammatory responses, depending on the situation. Recent structural and functional studies have revealed details of the structure of IgA and its interaction with key cell-surface receptors. We look at the role IgA and IgA receptors (particularly FcalphaRI) play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 123 publications
1
12
0
Order By: Relevance
“…Besides IgG Abs, IgA Abs also play an important role in humoral immunity. IgA interacting with IgA receptors (particularly FcαR) has been found to affect pathogenesis of diseases and autoimmune conditions (18). However, immunogenetic variation of FcγRs and FcαRs in immune responses to and clinical protection by vaccines in humans remains under investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides IgG Abs, IgA Abs also play an important role in humoral immunity. IgA interacting with IgA receptors (particularly FcαR) has been found to affect pathogenesis of diseases and autoimmune conditions (18). However, immunogenetic variation of FcγRs and FcαRs in immune responses to and clinical protection by vaccines in humans remains under investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that circulating neutrophils from DH patients show evidence of partial priming including the increased function of IgA FcRs [7] and in this way neutrophils show an increased ability to bind IgA. Literature data [10][11][12] postulated that FcRs play a crucial role in the activation and/or down-regulation of immune responses and thus, their ligation with pathogenic autoantibodies may have results in tissue damage, including blister formation in autoimmune blistering dermatoses [13]. The mechanism of inflammatory induction probably involves structural/conformation alternation of FcRs and modification of their activating/inhibitory functions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several known receptors for IgA, although few were characterized in much detail [2]. The best known IgA FcRs include the polymeric IgG receptor (pIgR), FcαRI (CD89), and Fcα/µR [11]. Recently, also the role of CD71 in the pathomechanism of IgA-mediated diseases was noticed [14].…”
Section: Introductionmentioning
confidence: 99%
“…1,13,16,19,[122][123][124][125] Thus, future therapeutic strategies depend on our detailed understanding of the molecular mechanisms underlying MIRR triggering and subsequent TM signal transduction. In addition, understanding these mechanisms would give us a new handle in dissecting the basic structural and functional aspects of the immune response.…”
Section: School Model Of Multichain Receptor Signalingmentioning
confidence: 99%